2020
DOI: 10.1186/s12888-019-2414-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental levels of stress managing a child diagnosed with type 1 diabetes in Riyadh: a cross sectional study

Abstract: Background: Caring for a child with Type 1 Diabetes (T1D) pose a significant burden on parents especially when they struggle with their child's T1D management. The experience of not coping or struggling to cope increases the level of stress in parents, which may adversely affect their child's diabetic control (Al Dubayee et al, Horm Res Paediatr 88:2019). In this study, we assessed the level of stress parents experience in caring for a child diagnosed with T1D in four different domains. Methods: This was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…According to the most recent epidemiological data in Italy, the onset of pediatric diabetes mostly occurs between 9 and 11 years of age [ 2 , 46 ]. In the context of pediatric diabetes, parents might be at greater risk of perceiving an intense level of parenting stress, due to their key role in the management of their child’s diabetes [ 12 ]. Most of the studies have focused on mothers’ parenting stress related to the children’s chronic illness, considering them as the primary caregivers involved in administering the insulin and the strict diet regimen [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the most recent epidemiological data in Italy, the onset of pediatric diabetes mostly occurs between 9 and 11 years of age [ 2 , 46 ]. In the context of pediatric diabetes, parents might be at greater risk of perceiving an intense level of parenting stress, due to their key role in the management of their child’s diabetes [ 12 ]. Most of the studies have focused on mothers’ parenting stress related to the children’s chronic illness, considering them as the primary caregivers involved in administering the insulin and the strict diet regimen [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggest that, where T1DM is concerned, the psychological functioning of parents and children are mutually related, thereby directly influencing each other [ 7 ]. In the specific case of parenting a child with T1DM, parenting stress is influenced by factors such as the responsibility felt toward the child’s diabetes-management and anxious states concerning the fear of hypoglycemia [ 8 , 9 , 10 , 11 ] as well as the frequency of hypoglycemia, the number of years since diagnosis and demographic variables such as marital status and education level [ 12 ]. Indeed, parents’ diabetes-specific stress can have repercussions on their well-being [ 4 ], and in turn on that of their children, thereby potentially influencing the child’s Hemoglobin A1c (HbA1c), and also on their depression symptoms [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies did not report parents' age. 24,[27][28][29][30][31] Nine of the 12 studies focused their analyses on parents and caregivers alone (reporting only demographic and clinical data from children), [9][10][11][23][24][25][26]30,31 while three studies reported results from both parents and children. [27][28][29] The mean ± SD age of children ranged from 5 ± 2 to 15 ± 2 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Two studies did not provide a definition of or recall period for hypoglycaemia, and only reported on the frequency of hypoglycaemia. 24,26 Table 2 summarizes the definitions and measures of hypoglycaemia.…”
Section: Definition and Measurement Of Hypoglycaemiamentioning
confidence: 99%
See 1 more Smart Citation